What is the coefficient of x in the expansion of ( x + 3 ) 2 ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
( x + 3 ) 2 = x 2 + 6 x + 9 ⟹ 6
( x + 3 ) 2 = 2 ( 3 x ) = 6
In general:
( x + a ) 2 = x 2 + 2 ( a x ) + a 2
What do you think? @Brilliant Mathematics
Log in to reply
Hi Yajat. ( x + 3 ) 2 = 2 ( 3 x ) is not an algebraic identity. Consider x = 0 . The left-hand-side is equal to 9, but the right-hand-side is equal to 0.
Log in to reply
No. Just using algebra, is this true?
Log in to reply
@Yajat Shamji – Hi Yajat, ( x + 3 ) 2 is equal to x 2 + 6 x + 9 , but it does not equal to 2 ( 3 x ) .
No assigning values.
Problem Loading...
Note Loading...
Set Loading...
( x + 3 ) 2 = x × x + 2 × 3 × x + 3 × 3 = x 2 + 6 x + 9 .
Hence, the coefficient of x is 6.